Hepatic alveolar echinococcosis simulating metastatic malignancy - Suvradeep Mitra; Payal Charaya; Shrinath Gururaj Deshpande; Mayur Parkhi; Thakur Deen Yadav (University of São Paulo, 2024)
Echinococcosis is a parasitic disease caused by infection with tiny tapeworms of the genus Echinococcus. Echinococcosis is classified as either cystic echinococcosis or alveolar echinococcosis. The common form is a zoonosis from goats and sheep that tends to cause liver lesions. The larval stage of Echinococcus multilocularis causes alveolar echinococcosis/alveolar hydatid disease. It is a zoonosis with field mice and tundra voles as intermediate and wild carnivores like foxes and wolves as definitive hosts. This zoonosis is highly uncommon compared to the other form known as cystic echinococcosis but poses a great human threat if untreated. We report the case of a young man who was working in the Kashmir Valley, North India, and presented with jaundice and right upper quadrant abdominal pain. Computed tomography revealed a large solid-cystic intrahepatic lesion measuring 125x118x123 mm, suggestive of a malignant tumor with central necrosis. A liver biopsy showed necrosis with PAS-positive membranes morphologically consistent with echinococcosis. Alveolar echinococcosis can present as a solid-cystic mass in the liver and can simulate metastatic malignancy.